2020
DOI: 10.1186/s12934-020-01430-0
|View full text |Cite|
|
Sign up to set email alerts
|

Gut microbial characteristics of adult patients with allergy rhinitis

Abstract: Background Although recent studies have indicated that intestinal microbiota dweller are involved in the pathogenesis of allergy rhinitis (AR), the influence of gut microbiota on AR adult has not been fully elucidated yet. Hence, we carried out this study to uncover the distinctive bacterial taxa that differentiate allergy rhinitis patients from healthy individuals. Feces samples from thirty three AR patients and thirty one healthy individuals were analyzed by 16S rRNA gene sequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 47 publications
(68 reference statements)
3
50
0
1
Order By: Relevance
“…Generally, gut microbiota is dynamically diverse within limits and influenced by multiple factors such as species, age, sex, diet, and health status ( Manichanh et al, 2012 ; Wang et al, 2020 ; Xiong et al, 2020 ; Zhu et al, 2020 ). Several studies have indicated that diarrhea was able to cause a significant decrease in the diversity of gut bacterial community as well as shifts in intestinal functions ( Barash et al, 2017 ; He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, gut microbiota is dynamically diverse within limits and influenced by multiple factors such as species, age, sex, diet, and health status ( Manichanh et al, 2012 ; Wang et al, 2020 ; Xiong et al, 2020 ; Zhu et al, 2020 ). Several studies have indicated that diarrhea was able to cause a significant decrease in the diversity of gut bacterial community as well as shifts in intestinal functions ( Barash et al, 2017 ; He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a complete microbiome analysis to detect the impact of CPM +X on the microbiome was not conducted, which is one of the study limitations. However, the impact of the microbiome in the pathogenesis of AR should not be overlooked as it has been gaining attention among researchers in the allergy and immunology fields [4,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment was undertaken via screening patients who randomly visit the authors' (LZ) TCM clinic or (LT and BY) otorhinolaryngology clinic. The inclusion and exclusion criteria for AR subjects were the same as the previous study (2). Treatment was delivered in the usual setting of the authors' (LZ) TCM clinic in Xiamen University Hospital (Xiamen, China).…”
Section: Methodsmentioning
confidence: 99%
“…The complex ecosystem of the commensal microbiota and its interactions with the host are fundamental in determining health (1). Gut microbiota imbalance has been associated with allergic disease, including allergic rhinitis (AR) (2,3). AR is characterized as an immunoglobulin E (IgE)mediated inflammatory response of the nasal mucous membranes after exposure to inhaled allergens, which is estimated to affect nearly one in every six Americans and generates $2 to $5 billion in direct health expenditures annually (4,5).…”
Section: Introductionmentioning
confidence: 99%